Recognition of Traditional Villages as Local Government Administrators in Indonesia Based on the Principle of Autonomy - Muhtadli Muhtadli (Fakultas Hukum Universitas Lampung, 2020)
The state recognizes and respects units of regional government that are special or special in nature. This recognition and respect is valid until the customary law community and their traditional rights are still alive and in accordance with the development of society and the principles of the Unitary State of the Republic of Indonesia as referred to in Article 18 B paragraph (2) of the 1945 Constitution of the Republic of Indonesia. The state for village autonomy along with its traditional rights is an embodiment of the constitutional provisions in the form of regulating customary villages in the Indonesian government system as stipulated in Law Number 6 of 2014 concerning Villages. Efforts to strengthen the recognition of customary villages need to be realized in the legal politics of regulating customary villages that are just and constitutional so that customary villages can be realized in real terms. This study aims to analyze whether the legal politics of customary village recognition in regional governance is based on the principle of autonomy in Indonesia and its implementation. The method used is empirical normative legal research with a statutory approach and concepts and field studies. The results of the research and discussion show that the legal politics of customary village recognition in the implementation of regional government based on the principle of autonomy in Indonesia is a constitutional mandate and legislation that must be carried out by all parties consequently and fairly. Objectively, Article 18 B paragraph (2) of the 1945 Constitution of the Republic of Indonesia and Law Number 6 of 2014 concerning Villages have fundamental policy directions to strengthen the existence of traditional villages and their traditional rights in a consistent and fair manner in the Indonesian government system.